Allergic adverse events following immunization: Data from post-marketing surveillance in Apulia region (South of Italy) - Stefanizzi, Pasquale; Ferorelli, Davide; Scazzi, Francesco Livio; Di Lorenzo, Antonio; Martinelli, Andrea; Trinchera, Chiara; Moscara, Lorenza; Miniello, Enrico; Di Bona, Danilo; Tafuri, Silvio (Frontiers in Immunology, 2023)
Among adverse events following immunization (AEFIs), allergic reactions elicit the most concern, as they are often unpredictable and can be life-threatening. Their estimates range from one in 1,000,000 to one in 50,000 vaccine doses. This report describes allergic events following immunization reported from 2020 to 2021 in Puglia, a region in the South-East of Italy with around 4 million inhabitants. Its main objective is to describe the allergic safety profile of currently employed vaccines. This is a retrospective observational study. The study period spanned from January 2020 to December 2021, and the whole Apulian population was included in the study. Information regarding AEFIs reported in Puglia during the study period was gathered from the Italian Drug Authority’s pharmacovigilance database. The overall number of vaccine doses administered was extrapolated by the Apulian online immunization database. Reporting rates were calculated as AEFIs reported during a certain time span/number of vaccine doses administered during the same period. 10,834,913 vaccine doses were administered during the study period and 95 reports of allergic AEFIs were submitted to the RNF (reporting rate 0.88/100,000 doses). 27.4% of the reported events (26/95) were classified as serious (reporting rate 0.24/100,000 doses). 68 out of 95 (71.6%) adverse events were at least partially resolved by the time of reporting and none of them resulted in the subject’s death. Allergic reactions following vaccination were rare events, thus confirming the favourable risks/benefits ratio for currently marketed vaccines.